Social Capital Sports Oriented and Workersâ Participation in Tehran Newspaper - Alam, Shahram; Gholizadeh, Abbas (Journal of Educational, Health and Community Psychology, 2018)
AbstractÂ This present study examined the role of social capital sport oriented on workersâ participation in Tehran newspaper. Sport assumed as one of the principal factors in physical health that can be brilliant via difference items; furthermore, social-cultural is one of them. Besides, recognizing the main role of social-cultural on participation and also the motivation of workers is very necessary. On the other hand, lack of consideration to sportâs supportive factors appears many worries. In the current study, the sample of study was concentrated on 400 workers in Tehran newspaper. The questionnaire has comprised two main parts for assessing demographic factors and social capital sport oriented were applied. The result revealed that social capital sport oriented has a meaningful relationship with workers participation in physical exercises. As well, patterns champion determined as a key reason for sport amongst workers. Regarding the main role of sport in workers life, considering to the enhancing factors such as social capital is precious. By the way, the supervisors of workers should be established appropriate methods for workersâ participation in sport; likewise, stimulate them in sports accomplishments.Â Keyword: Physical activity, social capital, sport, and workersâ participationÂ